Law, terrorism and the right to know - McNamara, Lawrence (UK Data Service, 2014)
Law, Terrorism and the Right to Know (LTRK) was a three year research programme funded by the ESRC and AHRC under the RCUK Global Uncertainties Fellowships in Ideas and Beliefs scheme. The programme explored democratic traditions of media freedom and the contemporary demands of national and international security. It looked especially at the ways governments and courts deal with security related matters, and the relationships between the state and the media. It examined matters such as the ways that different parties involved in controlling access to, and the communication of, information see the relationships between principles of open justice, the rule of law, public accountability and national security. It explored how much and in what ways access to information is closed down and what the effects of this might be. It also aimed to look beyond whether there is a chilling effect in the traditional sense of increased self-censorship, to the broader impact of the legal framework on the ways that information can be selectively and strategically presented or concealed, and the respective roles of the state and the media in these processes. A core component of the work was a series of confidential research interviews. These were conducted over around 18 months in 2010-2012. Interviewees were drawn from the judiciary (with the support of the office of the Lord Chief Justice), government (including the Home Office, Cabinet Office, the Office of Counter-Terrorism and Security, the Ministry of Defence, and specialist units within government), the Association of Chief Police Officers and police forces, the Crown Prosecution Service and criminal defence lawyers, and a range of journalists, media lawyers and editorial decision-makers. Most interviews were done in the UK and the interviewees were from the UK. A small number of interviews were done in the US and Australia with individuals from those countries. The collection includes an explanatory note, the information and consent form, a list of transcripts by randomised code, and the collection of 65 interview transcripts. These cover 70 interviewees, as some interviews were done with two interviewees. This is almost the complete set of interviews. One further interview was done but I was not given permission to record it and thus there is no transcript. With one exception, the transcripts are very heavily redacted. While unfortunate for anyone wishing to use them in future, this was unavoidable. The exception is transcript LTRK-063. Further detail is in the "data sourcing, processing and preparation" information. A complex, far-reaching, legal framework governs the way information about terrorism is obtained by the media and conveyed to the public. Counter-terrorism legislation is important, but so are defamation, contempt, official secrets, freedom of information, free speech rights, the protection of journalists' sources, and the legal and ethical rules surrounding how lawyers deal with the media. This research programme aims to examine, within that framework, how democratic traditions of media freedom which characterise and sustain our liberal democracy through open, informed public debate - the basis of the public's right to know - can best be balanced against the contemporary demands of national and international security. The first of three linked projects looks at the media experience of reporting on terrorism. Using interviews with journalists and lawyers, the project will study the impact of the legal framework and consider also how agencies of the government manage and release information. The second project analyses legislative and judicial approaches to balancing openness and secrecy. The third project brings key stakeholders together at a conference to elicit and analyse their perspectives on how openness and secrecy should be balanced to achieve both liberty and security.